Tau Kinetics in Neurons and the Human Central Nervous System - Sato, Chihiro; Barthélemy, Nicolas R; Mawuenyega, Kwasi G; Patterson, Bruce W; Gordon, Brian A; Jockel-Balsarotti, Jennifer; Sullivan, Melissa; Crisp, Matthew J; Kasten, Tom; Kirmess, Kristopher M; Kanaan, Nicholas M; Yarasheski, Kevin E; et al. (Neuron (Cambridge, Mass.), 2018)
We developed stable isotope labeling and mass spectrometry approaches to measure the kinetics of multiple isoforms and fragments of tau in the human central nervous system (CNS) and in human induced pluripotent stem cell (iPSC)-derived neurons. Newly synthesized tau is truncated and released from human neurons in 3 days. Although most tau proteins have similar turnover, 4R tau isoforms and phosphorylated forms of tau exhibit faster turnover rates, suggesting unique processing of these forms that may have independent biological activities. The half-life of tau in control human iPSC-derived neurons is 6.74 ± 0.45 days and in human CNS is 23 ± 6.4 days. In cognitively normal and Alzheimer's disease participants, the production rate of tau positively correlates with the amount of amyloid plaques, indicating a biological link between amyloid plaques and tau physiology.